Increasing Access to Organization Theories for Implementation Science - Birken, Sarah A.; Ko, Linda K.; Wangen, Mary; Wagi, Cheyenne R.; Bender, Miriam; Nilsen, Per; Choy-Brown, Mimi; Peluso, Alexandra; Leeman, Jennifer (Frontiers in Health Services, 2022)
Background. Organization theories offer numerous existing, highly relevant, yet largely untapped explanations of the organizational dynamics underlying evidence-based intervention (EBI) implementation. Rooted in concepts of power, autonomy, and control, organization theories can explain how and why organizations adopt, implement, and sustain EBI use. Although they have gained visibility, organization theories remain underused in implementation research, perhaps due to their inaccessibility to implementation scientists. To improve access to organization theory among implementation scientists, we summarized organization theories with relevance to implementation science. Methods. Led by the Cancer Prevention and Control Research Network (CPCRN) Organization Theory for Implementation Science workgroup, we employed a modified Delphi process to reach a consensus among 18 experts at the intersection of organization and implementation science regarding organization theories with relevance to implementation science. From texts that described the organization theories, using standardized abstraction forms, two investigators independently abstracted information regarding constructs, propositions regarding how or why constructs might influence implementation, the potential relevance of organization theories’ propositions for implementation, and overviews of each theory. The investigators then reconciled discrepancies until reaching consensus. A third investigator reviewed reconciled abstraction forms for accuracy, coherence, and completeness. Findings. We identified 9 organization theories with relevance to implementation science: contingency, complexity, institutional, network, organizational learning, resource dependence, sociotechnical, and transaction cost economics. From the theories, we abstracted 70 constructs and 65 propositions. An example proposition from institutional theory is: “Coercive, mimetic, and normative pressures contribute to organizations…within an organizational field [becoming increasingly similar].” These organization concepts can be operationalized as levers to facilitate EBI implementation. Conclusions. To increase use in the field, organization theories must be made more accessible to implementation scientists. The abstraction forms developed in this study are now publicly available on the CPCRN website with the goal of increasing access to organization theories among an interdisciplinary audience of implementation scientists through the CPCRN Scholars program and other venues. Next steps include consolidating organization theory constructs into domains and translating the resulting framework for use among researchers, policymakers and practitioners, aiding them in accounting for a comprehensive set of organization theory constructs thought to influence EBI implementation.